The psychometric properties of the Turkish version of the smoking outcome expectation scale and the anti-smoking self-efficacy scale for early adolescents. (2nd November 2017) - Bektas, İlknur and Bektas, Murat and Ayar, Dijle and Kudubeş, Aslı Akdeniz and Selekoglu, Yasemin and Sal Altan, Sema and Çelik, İsa and Tuna, Arzu
ABSTRACT: This study aimed to analyze the validity and reliability of the Smoking Outcome Expectation Scale and Anti-Smoking Self-Efficacy Scale for Early Adolescents in Turkey. The sample of the study included a total of 548 students. The data were collected using a demographic data collection form, the Smoking Outcome Expectation Scale, and the Anti-Smoking Self-Efficacy Scale (ASSES) for Early Adolescents. ASSES consists of 15 items, and SOES consists of six items. The Cronbach's alpha coefficients of the ASSES section and its subscales were .93, .94, .89, and .75, respectively. These values were found to be.70, .85, and .91 in the SOES section and its subscales. Both sections' test–retest correlation coefficients were found to be higher than .25 for all items. The factor loads ranged between .45 and .76 in the ASSES section and between .87 and .95 in the SOES section. The goodness-of-fit indices of both sections were above .90, and their root mean square error of approximation (RMSA) values was <.08. These results indicate that the scale is a valid and reliable tool for use with early adolescents in Turkey.